Mapping the evolution of academic professional development: a bibliometric review (1973-2024) - Du, Yue; Hazri Jamil,; Siti Soraya Lin Abdullah Kamal, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Academic professional development (APD) is crucial for adjusting to evolving educational requirements, improving teaching effectiveness, and promoting research productivity. This bibliometric review (1973–2024), based on data from the Web of Science Core Collection and analysed using CiteSpace, identifies major contributors, emerging trends, and research priorities. It reveals that Irby, D.M. is the most prolific author, with the United States leading overall contributions. European countries stand out for strong national and institutional collaboration, promoting knowledge exchange and innovation. Co-occurrence and keyword cluster analyses highlight four main themes: student-centered competencies, organizational reform, APD assessment, and innovative methodologies and technologies. These themes reflect growing scholarly attention to more complex and systemic aspects of APD. Notably, there has been a shift from a traditional focus on medical education toward broader concerns, such as organizational transformation and policy alignment, suggesting a move toward a more holistic and integrated approach. The findings emphasize the need for adaptable, globally relevant APD strategies that respond to evolving challenges in higher education. This study provides future research directions and supports efforts to design more effective APD programs aligned with institutional and societal goals.